Morphological and functional retinal changes in postoperative hypotony - V.P. Erichev; A.A. Antonov; A.A. Vitkov; E.A. Ragozina; A.V. Volzhanin (РМЖ "Клиническая офтальмология")
V.P. Erichev, A.A. Antonov, A.A. Vitkov, E.A. Ragozina, A.V. Volzhanin Scientific Research Institute of Eye Diseases, Moscow, Russian Federation Aim: to analyze the retinal microvascular network changes in hypotony maculopathy after non-penetrating deep sclerectomy (NPDS). Patients and Methods: the study enrolled 35 patients (35 eyes) with uncontrolled glaucoma stages II and III in whom the intraocular pressure (IOP) level was less than 10 mm Hg after NPDS. In addition to a standard eye exam, all patients underwent optical coherence tomography angiography (OCTA) before and one day after surgery. In addition, the radial peripapillary capillary (RPC) network vessel density (VD) on 4×4-mm optic nerve scans, superficial vascular plexus (SVP) VD on 6×6-mm macular scans, and foveal avascular zone (FAZ) area on 3×3-mm scans were evaluated. Results: IOP-lowering effect was reported in all patients, i.e., IOP level reduced by, on average, 17.7±8.3 mm Hg. In 15 patients, baseline OCTA parameters worsened (group 1). In 17 patients, OCTA parameters improved (group 2). In 3 patients, OCTA parameters remained unchanged (group 3). In group 1, parafoveal VD reduced by 1.5% [2.45%; 0.85%] in the superior sector and 1.3% [1.75%; 0.85%] in the inferior sector. Peripapillary VD reduced by 0.6% [2.0%; 0.1%] in the superior sector and 1.1% [2.4%; 0.0%] in the inferior sector. In group 2, parafoveal VD improved by 0.85% [0.0%; 1.75%] in the superior sector and 1.2% [0.68%; 2.6%] in the inferior sector. Peripapillary VD improved by 1.2% [0.18%; 2.0%] in the superior sector and 0.95% [0.05%; 1.75%] in the inferior sector. IOP levels were similar. No correlations between OCTA parameters and IOP levels were revealed. Postoperatively, the FAZ area remained unchanged. Conclusions: postoperative hypotoni a has a positive and negative impact on the retinal microvascular network. OCTA findings after NPDS demonstrate no correlations with IOP levels. Further studies are needed to identify prognostic factors of hypotony maculopathy and assess its long-term effects on retinal vessels. Keywords: glaucoma, non-penetrating deep sclerectomy, hypotony maculopathy, OCTA. For citation: Erichev V.P., Antonov A.A., Vitkov A.A. et al. Morphological and functional retinal changes in postoperative hypotony. Russian Journal of Clinical Ophthalmology. 2021;21(4):187–193 (in Russ.). DOI: 10.32364/2311-7729-2021-21-4-187-193.